The Role of Health Cadres and Pregnant Women's Visits in Integrated Primary Service Post in Sidorahayu Village, Wagir District, Malang Regency - Yuliawati, Dwi; Wardhani, Ratih Kusuma; Mardiana, Heppy Rina (Asian Journal of Healthcare Analytics, 2025)
Primary Service Transformation of health services to the community is done to enhancement and reinforcement promotion, prevention for healthy in the life cycle. Health problems in mothers and babies are great, so attempts are be required to strengthen primary health services. The purpose of this study was to determine the relationship between the role of health cadres and visits by pregnant women at the Integrated Primary Service Post in Sidorahayu Village. This study presented an analytical cross-sectional study utilizing data from a questionnaire was conducted between November until December 2024. Samples were 25 pregnant woman. In the study, there is a relationship between the role of cadres and the compliance of pregnant women in visiting the Integrated Primary Service Post.